THE PROVISION OF HIGH-QUALITY FINANCIAL INFORMATION IN INCREASING VOLUNTARY DISCLOSURE - Hisar Pangaribuan; Endah Sri Wahyuni; Harsono Yoewono; Denok Sunarsi (Universitas Dharma Wacana, 2022)
Diverse parties require more extensive, pertinent, exhaustive, and timely information to aid decision-making. This research aims to determine how financial information quality (FIQ) affects voluntary disclosure (VD), particularly when it is moderated by corporate culture (CC). We employed two stages of data collection. The first stage was carried out by distributing questionnaires to company accountants, auditors, and educator accountants concerning the FIQ, CC, and VD. The selected respondents were considered competent with the intended research topic to obtain the respondents' objective and professional perceptions of the distributed questionnaires. The second stage was conducting semi-structured interviews with the competent participants to obtain their professional judgments on the variables studied. The data was processed using a variance-based approach to answer the constructed hypotheses. The study proposed that high-quality financial information could significantly influence the increase of VD. This study also showed that an opened CC could strengthen VD. The supervisory role of top management and the board is crucial to producing reliable, high-quality financial information and building a more open CC. It also influences the growth of VD, reduces information asymmetry, and increases capital market investment transactions.Â